Development of Yoga Intervention Module for Children and Adolescents with Major Depressive Disorder - Bichitra Nanda Patra; Rajesh Sagar; Gautam Sharma; Kanika Khandelwal; Ruchi Goswami (International Journal of Yoga)
Introduction: Mental health problems constitute around 7.5% of the global burden of disease. Worldwide, depression has been expected to be the second-leading cause of disability by 2020. Child and adolescent depression are associated with decreased school attendance, poor performance at school, use of drugs and alcohol, violence, and suicidal behavior. In recent times, various complementary and alternative medicines (CAMs) such as mindfulness and meditation intervention, acupuncture, nutraceuticals, and physical exercise have also gained interest with encouraging results. One such CAM intervention is Yoga. The current paper focused on the development and validation of yoga therapy. Materials and Methods: A yoga module was developed in three steps. The first step was the development of a yoga module where traditional texts, research papers were extensively reviewed. Based on that existing literature, a module was outlined. In the second step, the detailed module was validated by the experts in the field of yoga. In the third step, a pilot study was carried out on five participants and they were administered on depression scale for children. Moreover caregivers were also assessed on variables like depression, stress and anxiety at baseline and postassessment. Results: It was found that yoga therapy was acceptable among children and adolescents with major depressive disorder. There was high compliance among participants. They reported overall satisfaction and found a reduction in depression scores on the measures used. Discussion: Yoga therapy should be recommended by professionals in out-patient clinics. Moreover, this is a pilot-tested study and hence comment on the efficacy of the present study could not be made.